Outcomes of single‐dose peri‐procedural antibiotic prophylaxis for endoscopic ultrasound‐guided fine‐needle aspiration of pancreatic cystic lesions. Issue 5 (1st October 2014) - Marinos, Emmanuel; Lee, Sunny; Jones, Brian; Corte, Crispin; Kwok, Avelyn; Leong, Rupert W
Abstract : Background: Endoscopic ultrasound (EUS)‐guided fine‐needle aspiration (FNA) is a technique frequently used to diagnose solid and cystic lesions of the pancreas. Antibiotic prophylaxis has been recommended for EUS‐FNA of pancreatic cystic lesions but is not universally observed. The most effective antibiotic and the most efficacious route and regimen of administration are also unknown. Objective: This cohort study was undertaken to evaluate whether single‐dose piperacillin/tazobactam or ciprofloxacin given at the time of the procedure effectively prevents major adverse events and to audit the adherence to this protocol in the setting of EUS‐FNA of pancreatic cystic lesions. Design: Consecutive EUS‐FNA procedures of pancreatic cystic lesions were performed at Concord Hospital and significant variables regarding the procedure and adverse events were recorded. Patients were also contacted by telephone to follow‐up any subacute adverse events they may have experienced. Patients: Over a 30 month period (January 2010–July 2012), a total of 85 EUS‐FNAs of pancreatic cysts were performed on 80 different patients. The mean age was 63.2 years (range 17–89 years; 58% females). Interventions: Single‐dose piperacillin/tazobactam IVs was administered to 87% of patients, while 12% of patients received ciprofloxacin IVs. Results: No patients developed cyst infection, fever, or sepsis (0%) and one patient (1.2%) was hospitalised for self‐limited nausea without adverse sequelae. Conclusions: Single‐dose piperacillin/tazobactam at the time of EUS‐FNA of pancreatic cysts is an effective prophylaxis of cyst infection or sepsis and can be conveniently given as a single‐dose peri‐procedurally without further oral antibiotics.